Fa’aliyyatus Tikhdami Wasilati Anchor Podcast fi Watsapp ‘Ala Tarqiyyati Maharah Al Istima’ Bi Al Madrosah Al Mihniyyah Al Islamiyyah Smart Informatika Gremet Manahan Banjarsari Surakarta - Muhammad Alfi Shofa A’yuna; Maslamah; Imam Makruf; Zainul Abas; Fajar Shodiq (Lembaga Penelitian dan Pengabdian Masyarakat, Sekolah Tinggi Ilmu Bahasa Arab Ar Raayah, 2022)
ملخص البحث أهداف هذه الرسالة لتجربية استخدام وسيلة أينكور بودكاس (Anchor Podcast) في واتساب (WhatsApp) لمحاسبة درجة الطلاب في الفصل الضابط و التجريبي و لمعرفة فعاليته على ترقية مهارة الإستماع لدى الطلاب في الصف الحادي عشرة بالمدرسة المهنية الإسلامية (SMART INFORMATIKA). هذه الرسالة هي رسالة كمية ونوعها شبه تجريبية, مجتمع البحث هو كل التلاميذ في الصف الحادي عشرة مع عينة 40 تلاميذا. و أما جمع البينات بطريقة الإختبار والتوثيق والمقابلة. وأما إختبار أداوت البيانات بإختبار الصدق والثبات.و تحليل البينات بإختبار سوى البيانات و تجانس البيانات . ثم يستخدم الإختبار الفرصية إختبارا Paired Samle T Test بطريقة الإحصائية. و أما نتيجة الرسالة تدل أن في مجموعة التجريبية قبل وبعد التعليم ٬ ثم الحصول على القيمة المعنوية (2-Tailed) 0٬00. وهي أصغر من 0٬05 ففرضيته Ho مفروضة و Ha مقبولة٬ بمعنى هناك تأثير أو فعالي إيجابي كبير. ومن البيانات والدراجات السابقة في فصل التجريبي و الضابط تدل على أنّ استخدام تطبيق أينكور بودكاس (Anchor Poadcast) في وسيلة واتساب (WhatsApp) في تعليم بالشبكة الإنترنيت في اللغة العربية على ترقية مهارة الإستماع أكثر فعاليته من ذلك لدى الطلاب في الصف الحادي عشر بالمدرسة المهنية الإسلامية (SMART INFORMATIKA) قريمت ماناهان بانجارساري سوراكارتا. للسنة الدراسية 2021 – 2020 Abstract The purposes of this study that the first is to try out online learning using whatsapp with the help of the anchor podcast application, to calculate the value of students in the experimental and control classes, to find out the that effectiveness. This research is a quantitative research and the type is a quasi experimental study, The population in this study were all students of class XI with a sample of 40 students. And collection techniques using tests, documentation and interviews. And as for the instrument test using validity and reliability tests. And the classical assumption test uses normality and homogeneity tests. And for the final test using the paired sample T test using SPSS. The results showed that in the experimental class before and after learning, the score (2-Tailed) was 0.00. And the value is smaller than 0.05 then the hypothesis Ho is rejected and Ha is accepted. From the data and values ​​above, it shows that the use of the anchor podcast application in WhatsApp media in online learning of Arabic languange subjects towards increasing listening competence is more effective than not, in class XI at SMKIT Smart Informatika Gremet Manahan Banjarsari Surakarta for academic year 2020/2021